Microstructure & Tribological Performance of Alumina-3wt% Titania Coatings Produced by APS - DJENDEL, Mokhtar; ALLAOUI, Omar; MAAZOUZ, Mourad; BOUBAAYA, Rabah (International Journal of Computational and Experimental Science and Engineering, 2020)
Al2O3-3wt%TiO2 coatings were deposited by atmospheric plasma spraying (APS). The microstructure and phase composition of the coatings were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The wear and friction properties of Alumina–3wt.% titania coatings against a steel ball under dry friction conditions were examined. The microstructure result and the phase of the spray coating is analyzed and presented. In addition, wear behavior of the sprayed coating are evaluated for final coating performance. , test results showed that increasing some process parameters increased the performance of mechanical properties of coating and gave the lowest friction coefficient value of coating.